IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 TERHADAP KEDUDUKAN ANAK LUAR KAWIN - Indra Lesmana; Emilda Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Decision of the Constitutional Court Number 46/PUU-VIII/2010 is considered to have an influenceon the position of children outside of marriage as a follow-up to the non-issuance of the GovernmentRegulation which regulates the position of children outside marriage as mandated by Article 43 paragraph(2) of Law Number 1 of 1974 Based on rational justice, the Constitutional Court then changed the sound ofArticle 43 of Law Number 1 of 1974 to "Children born out of wedlock have a civil relationship with theirmother and mother's family and with men as fathers who can be proven based on science and technologyand/or other evidence according to law that has blood relations, including civil relations with his father".This study aims to determine the implications of the Constitutional Court Decision Number 46/PUUVIII/2010 for the position of out-of-wedlock children, and the difference with the position of out-of-wedlockchildren prior to the Decision.This research is a normative legal research, because it is based on library research that takesexcerpts from reading books, literature, or supporting books that have relation to the problem to be studied,assisted with primary, secondary and tertiary data sources. This study uses qualitative data analysis andproduces descriptive data.From the results of the study, it was concluded that, First, before the Constitutional Court DecisionNumber 46/PUU-VIII/2010 out-of-wedlock children could have a civil relationship with their biologicalfather through child recognition (Articles 272-279 of Burgerlijk Wetboek) and child endorsement (Articles280-289 of Burgerlijk Wetboek). Second, the Constitutional Court Decision Number 46/PUU-VIII/2010 onlyapplies to connecting civil relations of children outside marriage whose marriages of both parents arehindered by the provisions of Article 2 paragraph (2) of Law No. 1 of 1974 concerning Marriage, while forextramarital chidren whose biological parents have never been married, Constitutional Court rulingNumber 46/PUU-VIII/2010 is used as a last alternative as long as voluntary recognition and/or ratificationcannot be carried out in order to hold the biological father responsible for the child outside or marriage.The author's suggestion is, First, that the Government immediately issues a Government Regulationgoverning the position of out-of-wedlock children as mandated by Article 43 paragraph (2) of Law No. 1 of1974 concerning Marriage. Secondly, so that Constitutional Court Decision Number 46 / PUU-VIII / 2010is not to be misinterpreted so that it will legalize adultery.Keywords: Constitutional Court Decision - Implications - Children Out of Wed